(untitled) (Sirte University Journal of Humanities, 2026)
This study analyzes accessibility from Queen Alia International Airport to major tourist destinations in Jordan using the Location Allocation model and network analysis within a Geographic Information Systems (GIS) environment. It evaluates travel distance, time, and cost to assess the efficiency of the tourism transport network based on data up to 2025. The results indicate that most tourist destinations fall outside the effective coverage of public transportation, leading to increased travel time and cost for visitors. The nearest destination, Jabal Al-Qalaa, is located approximately 44 km from the airport with a travel cost of 22.5 JOD, while the farthest destination, Aqaba, reaches about 306 km with a cost of 112 JOD. Petra also shows relatively high accessibility cost and distance at approximately 204 km and 77 JOD. The study highlights a clear relationship between distance and travel cost, emphasizing the spatial challenges affecting accessibility to remote tourist sites. It recommends improving tourism transport services by introducing organized and subsidized transportation linking the airport to key destinations, thereby reducing travel burdens and enhancing Jordan’s competitiveness as a tourist destination.